The (still) Unresolved Question of COVID-19 Passes Compatibility with the ECHR. Comments on the ECtHR Decision of 7 October 2021 in Zembrano v. France (Application no. 41994/21) - Kapelańska-Pręgowska, Julia (Polish Review of International and European Law, 2022)
This article analyses the question of compatibility of COVID-19 passes with the European Convention of Human Rights. The present commentary’s point of reference is the European Court of Human Rights inadmissibility decision in Zembrano v. France. Nevertheless, the main focus is not given to the admissibility criteria but to the more general considerations concerning restrictions of individual rights and freedoms introduced in the context of the current pandemic. The article offers some insights into the necessity and proportionality of an interference (the COVID-19 pass requirement). It also discusses if such measures are discriminatory or not